Obesity, neural tube defects and folic acid—A complex relationship - Gideon Koren; Yusuf C Kaplan (Clinical and Experimental Obstetrics & Gynecology)
Obesity is associated with twofold increased risk of neural tube defects (NTD). Research has repeatedly shown that about 70% of NTD are folic-acid dependent. Yet, there is controversy whether folic acid status is the main determinant of the increased risk of obesity-induced NTD. The rational for this review is to update and discuss the evidence on the link between obesity, folic acid and NTD, in an attempt to shed light on the question whether optimal folic acid dose schedule can mitigate this risk. During pregnancy maternal folate requirements increase by 5–10-fold, as folate is diverted towards the placenta and fetus, as well as supporting different maternal organs. Correspondingly, low maternal folate status has been associated with birth defects in fetal anatomical regions particularly sensitive to reduced folate intake including oral cleft, cardiovascular defects and NTD. A recent study has documented decreased placental folate transporter expression and activity in the first and second trimesters among obese mothers. This may explain the higher incidence on NTD in infants of obese women, as less folate may find its way to the developing fetus during the sensitive periods for creating NTD. Recent pharmacokinetic results indicate that steady state levels of folate are almost perfectly defined by the dose per lean body weight (LBW). The mean dose per kg LBW that would be expected to result in steady state serum folate level of > 15.9 nmol/L was identified as 0.0073 mg/kg LBW. A large study found no differences in dietary supplementations of folic acid, yet obese women exhibited lower median serum folate as well as lower mean serum B12 levels, but no differences in mean RBC folate levels. There was a negative correlation between increasing BMI and both serum folate and plasma B12. Future research will be needed to incorporate more fully, in addition to evidence of NTD, obesity and folic acid intake, also direct measurements of serum and RBC folate, as well as other confounders, in order to create a model that will shed light on these complex interactions.